Synthesis and characterizations of composite based on cu2o zno-polyaniline for removal of Conco Red Dye - Abdussamad Mukhtar Mohammed, 1989- 639403; Madzlan Aziz, supervisor 263346; Farhana Aziz, 1984-, supervisor 302491; Fakulti Sains 8004 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2021)
Thesis (Doktor Falsafah (Kimia)) - Universiti Teknologi Malaysia, 2021